Tubules composed of non-structural protein NS1 of african horsesickness virus as system for the immune display of foreign peptides - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2010.